2012
DOI: 10.2174/156720512800107537
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Dependent Levels of Hyaluronic Acid in Cerebrospinal Fluid of Patients with Neurodegenerative Dementia

Abstract: Numerous reports over the years have described neuroinflammatory events and vascular changes in neurodegenerative diseases such as Alzheimer´s disease (AD) and dementia with Lewy bodies (DLB). Interestingly, recent reports from other research areas suggest that inflammatory and vascular processes are influenced by gender. These findings are intriguing from the perspective that women show a higher incidence of AD and warrant investigations on how gender influences various processes in neurodegenerative dementia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 60 publications
1
11
0
Order By: Relevance
“…Consistently, reports of CSF and plasma concentrations of hyaluroinic acid, an adhesion molecule known to regulate both vascular and inflammatory processes, was found to be higher in patients with DLB as compared with cognitively normal and age-matched controls. 50 Taken together, these data suggest that DLB patients experience a robust inflammatory response and vascular abnormalities, which further exacerbate Lewy body-induced neuropathology.…”
Section: Dementia With Lewy Bodiesmentioning
confidence: 83%
“…Consistently, reports of CSF and plasma concentrations of hyaluroinic acid, an adhesion molecule known to regulate both vascular and inflammatory processes, was found to be higher in patients with DLB as compared with cognitively normal and age-matched controls. 50 Taken together, these data suggest that DLB patients experience a robust inflammatory response and vascular abnormalities, which further exacerbate Lewy body-induced neuropathology.…”
Section: Dementia With Lewy Bodiesmentioning
confidence: 83%
“…Studies performed by us and others have demonstrated increased levels of HA in CSF from individuals with pathologic changes in the brain vasculature [9,10]. In the current study, we aimed to investigate whether the level of HA in CSF could function as a clinical diagnostic marker for VaD and thus we measured HA levels in a new patient cohort consisting of patients clinically diagnosed with AD and VaD and controls without dementia.…”
Section: Discussionmentioning
confidence: 98%
“…Increased levels of HA in CSF from stroke patients have been reported [9]. In addition, we have recently demonstrated increased levels of HA in CSF from patients with Alzheimer's disease (AD) with vascular changes and a strong correlation between the levels of HA in CSF and Q-albumin (CSF/serum albumin ratio), an indicator of the function of the blood-brain barrier (BBB) [10]. To further investigate the potential diagnostic value of HA for vascular dementia (VaD), in this study we analyze HA in a new patient cohort consisting of controls without dementia and patients with AD and VaD.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In a recent study we also showed that CSF levels of ICAM-1 in female AD patients correlated with levels of hyaluronic acid, an adhesion molecule implicated in both inflammatory events and vascular changes. 97 The main significance of the described altered levels of Ig-CAMs in AD requires further investigation as neuroinflammation in AD appears to take place without any apparent influx of leukocytes from the blood. 98 Thus, the altered levels of the soluble forms of Ig-CAMs may reflect inflammatory processes unrelated to cognitive performance (as assessed with MMSE).…”
Section: Cams In Ad Neuroinflammatory Eventsmentioning
confidence: 99%